Analisis rantai pasok dan rantai nilai komoditas cabai Provinsi Jambi menuju perdagangan antar pulau dan eskpor - Muhammad Ridwansyah; Rayandra Ashar; Fuad Muchlis; Muhammad Donal Mon; Sopyan Aldino; Mauwlana Syukron (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
Jambi Province has great potential in pursuing horticultural production such as chili, not only to meet people's needs, but also opportunities for inter-regional trade and export. This study aims to 1) to get an overview of the supply chain and value chain of horticultural product commodities in Jambi Province; 2) To determine the position of Jambi Province horticultural product commodities for inter-regional trade purposes (Jambi and Batam); 3) To formulate a trading strategy for horticultural commodities for Jambi and Riau Islands (Batam Island). This study uses a qualitative descriptive method and uses a SWOT analysis. The results showed that the horticultural value chain is divided into 2 activities, namely the main activity consisting of incoming logistiks (horticultural raw material input), operations (horticultural production process into semi-finished materials), logistiks (output), and horticultural marketing. Second, supporting activities consisting of horticultural production infrastructure, HR development, technology development, and marketing and sales. The right strategy to use is a progressive strategy, meaning that the internal conditions of the chili commodity in Jambi Province are at a developing and progressing stage.